Formulation and characterization of nanoparticles combination of binahong leaves and bay leaves as a thin oral herbal preparation for diabetes prevention - Eka Priana; Garnadi Jafar; R. Herni Kusriani; Intan Meilani; Ranti Fitriani (Institute of Computer Science (IOCS), 2026)
Diabetes mellitus is a chronic metabolic disease with a steadily increasing prevalence globally. Binahong leaves (Anrederacordifolia) and bay leaves (Syzygiumpolyanthum) contains flavonoids, such as kaempferol, which have the potential as antidiabetics, but its use is limited by the low solubility, stability, and bioavailability of the active compounds. This study aims to formulate and characterize a nanoparticle herbal medicine combining the two leaves using PlantCrystal technology, and develop it into an oral thin herbal preparation. The simplicia was processed through sorting, washing, drying, grinding, and sieving, then characterized and screened for phytochemicals. The nanoparticle herbal medicine was evaluated based on particle size, polydispersity index, zeta potential, and particle morphology. The membrane lysis release test showed an increase in the release of active substances compared to the simplicia. Furthermore, the formulation was developed into an oral thin herbal and evaluated for its physical properties, including organoleptic, water content, pH, film thickness, fold resistance, weight uniformity, and disintegration time.